Representation of Sumbang Duo Baleh’s Cultural Values: A Study of Poetry in the Form of Minang Classical Song Lyrics - Ninawati Syahrul (Universitas Pendidikan Indonesia, 2024)
As a product of the creative process, song lines or lyrics are also forms of poetry containing aesthetical and ethical values. Song lyrics and poetry are like two sides of the coin, intertwined. Classical Minang song lyrics as a cultural product of traditional Minang people are objects that contain moral messages and life values. The cultural values contained in the song texts come from the experiences and life realities of the people. This research aims to reveal the meaning and cultural values contained in classical Minang songs. The research method used is descriptive qualitative with a literary sociology approach/theory. The research results show that cultural values in the Minang song texts align with the life attitudes of the Minang people. The cultural values of the Sumbang duo Baleh in the song “Si Nona” composed by Syamsul Arifin and the song “Lamang Tapai” composed by Nuskan Syarif are the traditional songs providing advice for Minang young women in maintaining their positive self-esteem. The classical Minang songs can be used as a means to preserve cultural values in developing the morals of future generations. By understanding the texts of Minang regional songs, they will appreciate and maintain various elements of their ancestral culture, as a reflection of the identity of the Minang people and elements of national culture.